Between Tradition And Modernization: Attitudes To Women's Employment And Gender Roles In Croatia - Brajdić Vuković, Marija (2005)
The effects of maternal employment on attitudes toward gender roles and gender equality in a transitional (postcommunist) Croatian society. The impact of transition and the war in Croatia on the dynamics of gender role attitudes in the 1989-2003 period.